Analysis of imprinted gene expression and implantation in haploid androgenetic mouse embryos. (6th January 2014) - Hu, M.; Zhao, Z.; TuanMu, L.‐C.; Wei, H.; Gao, F.; Li, L.; Ying, J.; Zhang, S.
Summary The successful development of mammalian embryos requires both parental genomes. Nuclear transfer techniques have been adapted to generate uniparental embryos, which possess two sets of paternal or maternal genomes. These embryos fail to develop to term because of abnormal imprinted gene expression, which is not regulated by Mendelian inheritance. Uniparental embryos provide us with an important model to investigate imprinted gene function and ontogenesis. To evaluate the pre‐ and post‐developmental ability of haploid androgenetic mouse embryos, and to analyse the expression of imprinted genes Igf2r, Asb4 and Mest in haploid androgenetic/gynogenetic blastocysts, we produced the haploid mouse embryos using the enucleation technique, examined their development at 6.5 dpc and quantified gene expression by quantitative real‐time PCR. The results demonstrated that the developmental potential of haploid embryos was severely impaired and revealed that the haploid androgenones could induce the deciduas reaction, but failed to retain a live foetus at 6.5 dpc. Expression of imprinted genes Igf2r and Asb4 was unregulated in haploid androgenetic/gynogenetic blastocysts.